Small Molecules Bound to Unique Sites in the Target Protein Binding Cleft of Calcium-Bound S100B As Characterized by Nuclear Magnetic Resonance and X-ray Crystallography - Charpentier, Thomas H. (2009)
Structural studies are part of a rational drug design program aimed at inhibiting the S100B–p53 interaction and restoring wild-type p53 function in malignant melanoma. To this end, structures of three compounds (SBi132, SBi1279, and SBi523) bound to Ca(2+)-S100B were determined by X-ray crystallography at 2.10 Å (R(free) = 0.257), 1.98 Å (R(free) = 0.281), and 1.90 Å (R(free) = 0.228) resolution, respectively. Upon comparison, SBi132, SBi279, and SBi523 were found to bind in distinct locations and orientations within the hydrophobic target binding pocket of Ca(2+)-S100B with minimal structural changes observed for the protein upon complex formation with each compound. Specifically, SBi132 binds nearby residues in loop 2 (His-42, Phe-43, and Leu-44) and helix 4 (Phe-76, Met-79, Ile-80, Ala-83, Cys-84, Phe-87, and Phe-88), whereas SBi523 interacts with a separate site defined by residues within loop 2 (Ser-41, His-42, Phe-43, Leu-44, Glu-45, and Glu-46) and one residue on helix 4 (Phe-87). The SBi279 binding site on Ca(2+)-S100B overlaps the SBi132 and SBi523 sites and contacts residues in both loop 2 (Ser-41, His-42, Phe-43, Leu-44, and Glu-45) and helix 4 (Ile-80, Ala-83, Cys-84, Phe-87, and Phe-88). NMR data, including saturation transfer difference (STD) and (15)N backbone and (13)C side chain chemical shift perturbations, were consistent with the X-ray crystal structures and demonstrated the relevance of all three small molecule–S100B complexes in solution. The discovery that SBi132, SBi279, and SBi523 bind to proximal sites on Ca(2+)-S100B could be useful for the development of a new class of molecule(s) that interacts with one or more of these binding sites simultaneously, thereby yielding novel tight binding inhibitors specific for blocking protein–protein interactions involving S100B.